Spun by sorcery - Bretton, Barbara (Berkley Books, 2010)
Chloe is always losing things-but an entire town? Just when she was about to settle down in Sugar Maple with her soul-mate Luke MacKenzie, her Fae enemy Isadora strikes, and her new hometown is gone. Even the Book of Spells, her lifeline to magick, can't help her now. Just in the nick of time, her friend Janice roars up in Chloe's ancient Buick with Penny the cat and her yarn stash in tow. If she is going to save her home she has to go back to Salem, where family secrets and centuries- old feuds pull her into the fight of her life.